La influencia de la actitud del consumidor en la intención de uso de altavoces inteligentes en las personas de 18 a 35 años en Lima Metropolitana - Velezmoro Rocha, Andres (2024)
The study aims to determine how consumer attitude is related to the intention to use smart speakers in people between 18 and 35 years old in Metropolitan Lima. A quantitative, correlational, and random sampling method was used. The sample is made up of 101 people between 18 and 35 years old in Metropolitan Lima who use smart speakers. For data collection, the survey was used as a technique, and the questionnaire as an instrument, which was adapted from the author (Aiolfi, 2023) , and measuring intention to use with 3 items, consumer attitude with 3 items and the dimensions Perceived Usefulness, Perceived Ease of Use, Perceived Privacy Risk, Innovation, Perceived Enjoyment, Social Attraction and Task Technology Adjustment. with 26 items, all on a Likert scale from 1 to 5. Cronbach's alpha tests, factor analysis, tests normality, Spearman evaluation coefficient and multiple linear regression tests were used to analyze the data. The work concluded that consumer attitude is related to the intention to use smart speakers in people between 18 and 35 years old in Metropolitan Lima.